The Mechanism of Knowledge Associated Integration of Interdisciplinary Research Team Based on Absorption Ability - Jin Ziqi; Zhong Bowen; Wang Xiaohong; Jiang Hua (MATEC Web of Conferences, 2017)
Interdisciplinary research team (IDRT) to solve complex, major multidisciplinary problem, is an important organization form. Members thought fusion and multidisciplinary knowledge integration is the key of implementing interdisciplinary team sustainable competitive advantage. According to the theory of knowledge absorptive capacity, this paper has analyzed knowledge associated integration mechanism of interdisciplinary team. First, the paper analyses the characteristics of absorbing ability cognitive mediation, subject link together mechanism, dimension conversion mechanism and reciprocal decision mechanism. Second, this paper builds an absorption evolution model of knowledge associated integration of interdisciplinary research team. Finally, it simulates and analyzes the evolution characteristics of interdisciplinary team knowledge network, and proposes management strategy.